2010
DOI: 10.1002/14651858.cd007396.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Parenteral opioids for maternal pain management in labour

Abstract: Background-Parenteral opioids are used for pain relief in labour in many countries throughout the world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
10

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(44 citation statements)
references
References 164 publications
2
32
0
10
Order By: Relevance
“…reported that satisfaction with postoperative pain management was influenced more by patient involvement in decision‐making and maintenance of control, than by the type of analgesia and treatment techniques. Our study showed no significant difference between groups when feelings of coping and control during labour were examined (Table ); however, these findings are consistent with other studies reporting that pethidine negatively affected maternal outcomes, including increased nausea and vomiting, sedation, length of labour, and the woman's ability to adopt upright positions . In contrast, fentanyl administered via alternative routes was well tolerated and provided effective pain relief with few adverse effects: a finding consistent with our study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…reported that satisfaction with postoperative pain management was influenced more by patient involvement in decision‐making and maintenance of control, than by the type of analgesia and treatment techniques. Our study showed no significant difference between groups when feelings of coping and control during labour were examined (Table ); however, these findings are consistent with other studies reporting that pethidine negatively affected maternal outcomes, including increased nausea and vomiting, sedation, length of labour, and the woman's ability to adopt upright positions . In contrast, fentanyl administered via alternative routes was well tolerated and provided effective pain relief with few adverse effects: a finding consistent with our study.…”
Section: Discussionsupporting
confidence: 91%
“…Norpethidine has been associated with neuronal depression in the neonate for up to 60 hours after birth . There are few alternative pharmacological options for women, with choice limited to what is held at the different hospitals . Although research suggests that women experience superior satisfaction in pain management in labour with the use of opioids compared with non‐opioids, practitioners continue to debate which opioid and mode of administration is most effective …”
Section: Introductionmentioning
confidence: 99%
“…To allow women to make informed choices concerning pain relief, larger trials are needed . Recently, we published the RAVEL study that compared RPCA and EA for satisfaction with pain relief among women with a medium to high obstetric risk.…”
Section: Introductionmentioning
confidence: 99%
“…A recent Cochrane Review has been published looking at the effectiveness and side effects of intrapartum parenteral opioids. 18 Short-term follow-up studies did not show sequelae in children in their development up to 5 years. 19e22 We investigated the association between PethidineÒ use and the risk on smoking, drinking alcohol or drug abuse in offspring 20 years after birth.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 86%